2013
DOI: 10.1124/jpet.113.203976
|View full text |Cite
|
Sign up to set email alerts
|

Menthol Inhibits 5-HT3Receptor–Mediated Currents

Abstract: The effects of alcohol monoterpene menthol, a major active ingredient of the peppermint plant, were tested on the function of human 5-hydroxytryptamine type 3 (5-HT 3 ) receptors expressed in Xenopus laevis oocytes. 5-HT (1 mM)-evoked currents recorded by two-electrode voltage-clamp technique were reversibly inhibited by menthol in a concentration-dependent (IC 50 5 163 mM) manner. The effects of menthol developed gradually, reaching a steadystate level within 10-15 minutes and did not involve G-proteins, sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 72 publications
3
39
0
Order By: Relevance
“…Despite relatively small changes in chemical structure, the compounds examined displayed five distinct pharmacological effects on α7 nAChRs. These included effects typical of type I PAMs, type II PAMs, NAMs, SAMs and allosteric agonists [33] and it has been proposed that all of these pharmacological effects can arise from ligands binding to a broadly similar or overlapping site located within the previously identified intra-subunit transmembrane cavity A transmembrane binding site in nAChRs has also been proposed for monoterpine compounds such as menthol and propofol [116,117] and is consistent with evidence supporting a transmembrane binding site for monoterpines on other pentameric LGICs [143][144][145][146][147]. Affinity labelling studies with a photoreactive analogue of propofol identified three sites at which it bound within the transmembrane domain of muscle-type nAChRs, but concluded that the functionally relevant site for the inhibitory action of propofol was an intra-subunit site [117], similar to that described earlier for α7-selective allosteric modulators such as NS-1738, PNU-120596 and 4BP-TQS [30,139].…”
Section: Various Sites and Amino Acids Have Been Shown To Be Importanmentioning
confidence: 60%
“…Despite relatively small changes in chemical structure, the compounds examined displayed five distinct pharmacological effects on α7 nAChRs. These included effects typical of type I PAMs, type II PAMs, NAMs, SAMs and allosteric agonists [33] and it has been proposed that all of these pharmacological effects can arise from ligands binding to a broadly similar or overlapping site located within the previously identified intra-subunit transmembrane cavity A transmembrane binding site in nAChRs has also been proposed for monoterpine compounds such as menthol and propofol [116,117] and is consistent with evidence supporting a transmembrane binding site for monoterpines on other pentameric LGICs [143][144][145][146][147]. Affinity labelling studies with a photoreactive analogue of propofol identified three sites at which it bound within the transmembrane domain of muscle-type nAChRs, but concluded that the functionally relevant site for the inhibitory action of propofol was an intra-subunit site [117], similar to that described earlier for α7-selective allosteric modulators such as NS-1738, PNU-120596 and 4BP-TQS [30,139].…”
Section: Various Sites and Amino Acids Have Been Shown To Be Importanmentioning
confidence: 60%
“…Examples of such compounds include verapamil (Hargreaves et al, 1996), cannabinoids (Barann et al, 2002), cannabidiol (Yang et al, 2010), hydrocortisone (Corradi et al, 2011), menthol (Ashoor et al, 2013), and PU02 (6-[(1-naphthylmethyl)thio]-9H-purine) (Trattnig et al, 2012). A variety of positive allosteric modulators of 5-HT 3 Rs have also been identified, including alcohols (Zhou and Lovinger, 1996), 5-hydroxyindole (van Hooft et al, 1997) colchicine (de Oliveira-Pierce et al, 2009), and 5-chloroindole (Newman et al, 2013).…”
mentioning
confidence: 99%
“…However, although the menthol effects were reduced by atropine, the muscarinic receptors are not the target for menthol because carbachol-evoked contraction was unaffected by menthol, whilst a prejunctional regulation of acetylcholine release via involvement of adrenergic pathways is likely to occur (Amato et al, 2013). In the present study, we have investigated whether neural receptors or ionic channels proteins, which are known by the literature to mediate various menthol effects (Boesmans et al, 2011;Hans et al, 2012; Ashoor et al, 2013b), can be target responsible for menthol triggering gastric relaxant.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, menthol has been hypothesized to exert antiemetic properties by inhibiting the cationic influx through 5-HT 3 receptor (Heimes et al, 2011) and it has been demonstrated to be an allosteric inhibitor of 5-HT 3 receptors using electrophysiological and biochemical methods (Ashoor et al, 2013b;Walstab et al, 2014). 5-HT 3 receptors are expressed by enteric sensory neurons in the mucosal layer and in the nerve cell body of interneurons and motor neurons in the enteric nervous system (Galligan, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation